Rural class differentiation in Nigeria: Theory and practice - a quantitative approach in the case of Nupeland - Dirk Kohnert (Africa Spectrum, 1979)
The knowledge of social stratification within the peasantry is a decisive precondition of sustainable economic and political measures for an effective support of agricultural production in least developed countries. This is one of the reasons why also in Nigeria social scientist focus on the problem of rural social structures recently. Up to now it was considered uncontested truth that, although there is considerable social and economic differentiation between the so-called small peasants, there is no class formation within the West African peasantry. However, these conclusions may rather reflect misinterpretations of the class concept than the actual situation of the peasants. A critical review of common misinterpretations of the historic-materialist class concept lays the base for the proposition of a new methodology for an analysis of the Nupe peasantry and rural social spaces in Northern Nigeria. Applied to the results an empirical investigation of four Nupe villages in Northern Nigeria in 1976, the proposed model reveals the early stages of a rural capitalist development, notably among rice producing marsh farmers of Cis-Kaduna, despite barriers of the semi-feudal land tenure system still in vigour in Nupeland. Widespread assumptions on the predominance of social mobility as great social equalizer in Northern Nigeria are not backed by the available data. – – La différenciation des classes rurales au Nigeria: Théorie et pratique - une approche quantitative dans le cas du pays Nupe: La connaissance des couches sociales à l'intérieur de la paysannerie est une condition préalable décisive lorsqu'il s'agit d'appliquer à grande échelle des mesures de politique économique encourageant efficacement la production agraire des pays du tiers monde. C'est pourquoi que des sociologues se penchent depuis peu sur le problème de la structure sociale de la paysannerie au Nigeria également. Jusqu'ici on en venait toujours à la conclusion qu'il existe bien des profondes inégalités sociales et économiques entre les paysans, mais qu'on ne peut cependant parler d'une différentiation de classes. Cette conclusion reflète probablement moins la situation effective des paysans que plutôt une interprétation erronée du concept de classes. Un survol critique de fausses interprétations du concept de classes pose les fondements pour un nouveau approche d'analyse de l'espace rural au Nigeria. Appliqué à une enquête socio-économique de quatre villages du pays Nupe dans le Nigeria du Nord en 1976, ce modèle montre les premiers stades d'un développement capitaliste rural, en particulier chez les paysans du Cis-Kaduna - producteurs de riz — un développement qui acompte en dépit des obstacles du système semi-féodal actuel de la propriété foncière. Les hypothèses largement répandues concernant l'importance de la mobilité sociale en tant que moyen de compensation sociale ne sont pas appuyées par les données disponibles.
Additional information: Author's Version
Keywords: N37; Q15; Q12; Q17; O15; Z1; 330; rural class formation; Nigeria; rural development; Africa; African History; Ländliches Einkommen; Soziale Schicht; Afrika; Nigeria; Geschichte Afrikas